2013
DOI: 10.1016/j.athoracsur.2012.12.060
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Autonomic Nerve Stimulation in the Treatment of Heart Failure

Abstract: Research on the therapeutic modulation of cardiac autonomic tone by electrical stimulation has yielded encouraging early clinical results. Vagus nerve stimulation has reduced the rates of morbidity and sudden death from heart failure, but therapeutic vagus nerve stimulation is limited by side effects of hypotension and bradycardia. Sympathetic nerve stimulation that has been implemented in the experiment may exacerbate the sympathetic-dominated autonomic imbalance. In contrast, concurrent stimulation of both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 49 publications
(78 reference statements)
1
26
0
1
Order By: Relevance
“…Clinical data have shown that functional disorders of the autonomic nervous system (increased sympathetic activity or decreased vagus activity) are associated with arrhythmia [42][43][44]. HRV is a quantitative, noninvasive indicator of autonomic nervous function in the cardiovascular system [34,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data have shown that functional disorders of the autonomic nervous system (increased sympathetic activity or decreased vagus activity) are associated with arrhythmia [42][43][44]. HRV is a quantitative, noninvasive indicator of autonomic nervous function in the cardiovascular system [34,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Considering left heart failure, imbalance of cardiac autonomic activity is characterized by marked sympathetic hyperactivity and abnormally low parasympathetic level.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular abnormalities are associated with an imbalance in the cardiac autonomic nervous system, 14 typically, characterized by increased sympathetic activity and decreased parasympathetic (vagal) activity. 26 Chronic vagal stimulation therapy (VNS) is believed to improve the imbalance of cardiac autonomic control by increasing parasympathetic activity.…”
Section: Introductionmentioning
confidence: 99%
“…26 Chronic vagal stimulation therapy (VNS) is believed to improve the imbalance of cardiac autonomic control by increasing parasympathetic activity. Accordingly, vagus nerve stimulation therapy has been introduced as a novel therapy for chronic heart failure (CHF), 1, 49 and has demonstrated improvement in symptoms. 4, 6, 9 …”
Section: Introductionmentioning
confidence: 99%